Evaluasi dan Manajemen Infrastruktur Jaringan Lokal (LAN) pada Badan Penanggulangan Bencana Daerah (BPBD) Kabupaten Ciamis - Muhammad Rofik Aprizani; Najwa Syafa Syahidah; Helmy Dzulfikar (STEKOM PRESS, 2026)
The Regional Disaster Management Agency (BPBD) of Ciamis Regency is an emergency institution that heavily relies on internet connectivity to support its operational functions, particularly in accessing disaster reporting applications. However, the existing local area network (LAN) infrastructure faces structural issues, including the absence of a structured failover mechanism, bandwidth management that lacks operational priority, and network segmentation without logical separation at the network layer. This study aims to evaluate the existing LAN infrastructure and formulate improvement recommendations using the first two stages of the Network Development Life Cycle (NDLC): Analysis and Design. Data were collected through direct observation and interviews with network administrators at the site. Evaluation results indicate that the primary issue lies not in bandwidth capacity, but in the governance layer and network distribution architecture. The proposed recommendations include implementing a Dual WAN topology with automatic Netwatch-based failover, tiered Simple Queue based on operational priority, VLAN-based network segmentation, and replacement of the hub with a managed switch. All recommendations are designed to be implemented using existing devices without requiring comprehensive new infrastructure procurement.